“It all depends on the project”—A business ecosystem in residential wooden multistory construction in Finland - Toppinen, Anne; Aaltio, Anniina; Lähtinen, Katja; Jussila, Jaakko; Toivonen, Ritva (Frontiers in Built Environment, 2022)
Using wood in multistory apartment construction (WMC) has a climate-positive advantage with buildings acting as long-term carbon storage. Business ecosystem (BE) development around WMC is needed to accelerate the adoption of wooden materials in the conservative construction industry. As the business actors around WMC are essentially different from those using other building materials, new knowledge must be built from the project level. This study uses a qualitative interview approach among actors from three pioneering urban building projects to address their perceptions of building with wood regarding a project-based BE. Based on the thematic analysis, sources of both tangible and intangible value creation were found to arise from building with wood. A higher degree of prefabrication associated with WMC was seen in all projects to influence the reorganization of logistics, enabling faster building processes and lean material use. No strong sustainability-driven culture could be identified in any of the projects. Results further flag the sensitivity and importance of management and coordination skills in targeting improvements of the construction business based on WMC. In the bigger picture, there is still room for further research at regional and global level on business model changes in building with this renewable and recyclable material.